Iron status in women using oral contraceptives (Bangladesh Journal of Physiology and Pharmacology, 2014)
Objectives: To assess the iron status of women using oral contraceptive pill (OCP) and compare this status with that of women of non-OCP users. Methods: This prospective cross-sectional comparative study was done in Dhaka Medical College from January 2006 to December 2006. Total 61 apparently healthy women of low socioeconomic class, age ranged 20-40 years were selected from different areas of Dhaka city. Of them 41 women were OCP users (Study group) and 20 women were non-OCP users (for comparison). OCP users again subdivided into subgroups according to duration of OCP use. Serum ferritin and haemoglobin level were taken as parameters of iron status in both groups. Statistical analysis was done by the SPSS 12.0 programme. Results: The mean (±SD) of serum ferritin level were 59.45±24.79ng/ml and 77.36±35.16 ng/ml in non-OCP & OCP users respectively. The difference of mean (±SD) of serum ferritin levels were significant (p: